Analisis Pengelolaan Administrasi dan Keuangan Berbasis Sistem Digital pada PERUM LPPNPI AirNav Indonesia Cabang Tanjungpinang - Anggifitri Fadillah; Irena Pradevy; Ismail Sati Alom Harahap; Aulia Rahman (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
This study aims to analyze the implementation of digital-based administration and financial management at Perum LPPNPI (AirNav Indonesia) Tanjungpinang Branch and examine its compliance with Sharia management principles, specifically amanah (trust) and accountability. Through a qualitative descriptive approach with observation, interviews, and documentation conducted during the Merdeka Belajar Kampus Merdeka (MBKM) program, this research highlights how modern enterprise systems like SAP Logon, e-Chain, and Arsipku reduce financial errors and bureaucratic delays. The results indicate that digital integration facilitates strict internal controls, accurate tax compliance (VAT and Income Tax), and organized operational data logging. From a Sharia perspective, this systematic digital tracking embodies the implementation of professional accountability (mas’uliyah) and financial stewardship (amanah), as it minimizes human error and guarantees transparency. This research contributes to the literature on public sector financial management by bridging the gap between state-owned enterprise digitalization and ethical Islamic business governance.